2015
DOI: 10.3389/fmicb.2015.00025
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of lettuce rhizosphere and roots by tagged Streptomyces

Abstract: Beneficial microorganisms are increasingly used in agriculture, but their efficacy often fails due to limited knowledge of their interactions with plants and other microorganisms present in rhizosphere. We studied spatio-temporal colonization dynamics of lettuce roots and rhizosphere by genetically modified Streptomyces spp. Five Streptomyces strains, strongly inhibiting in vitro the major soil-borne pathogen of horticultural crops, Sclerotinia sclerotiorum, were transformed with pIJ8641 plasmid harboring an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 62 publications
0
64
1
1
Order By: Relevance
“…Lastly, research to develop methods of bioinoculant delivery and timing must be carried out in the greenhouse and field to maximize the plant response to the applied bioinoculant. It has been found that applying streptomycetes is different to applying Gram-negative bacteria because better plant responses have generally been obtained when the streptomycete application to the soil or substrate occurred before sowing the seeds, thus allowing the selected strain to colonize and establish [6,137,138].…”
Section: Biotechnological Application Of Pgps In Agriculturementioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, research to develop methods of bioinoculant delivery and timing must be carried out in the greenhouse and field to maximize the plant response to the applied bioinoculant. It has been found that applying streptomycetes is different to applying Gram-negative bacteria because better plant responses have generally been obtained when the streptomycete application to the soil or substrate occurred before sowing the seeds, thus allowing the selected strain to colonize and establish [6,137,138].…”
Section: Biotechnological Application Of Pgps In Agriculturementioning
confidence: 99%
“…Since the endophytic compartment represent a more protective niche for plantbacteria interaction, formulations based on endophytic streptomycete strains had advantages over non-endophytic streptomycetes that would guarantee successful positive plant host response [139]. Representative streptomycetes possess the ability to colonize the rhizosphere or endophytic tissues of plants [6,87], to produce spores resistant to irradiation, heat, and drought [12], and to have an impressive range of metabolites with a variety of biological activities [140]. Streptomyces may also convert plant exudates or macromolecules/supramolecules present in the rhizosphere into a form that can be used by other plant growth-promoting microbes.…”
Section: Biotechnological Application Of Pgps In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…In agriculture, numerous Streptomyces species have demonstrated capability of controlling diverse fungal phytopathogens of great agroindustrial impact (Samac and Kinkel, 2001;Taechowisan et al, 2003;Tian et al, 2004;Khamna et al, 2009;Zarandi et al, 2009;Gopalakrishnan et al, 2011;Li et al, 2012;Kanini et al, 2013). However, relatively few biological inoculants have been developed for crop use, mainly based on the poor association between the efficiency determined in the laboratory compared to the one observed in the greenhouse or the field (Bonaldi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several markers were developed to study localization and quantification of PGPR: (i) antibiotic resistance (Gamalero et al 2003;Bonaldi et al 2015) and (ii) fluorescent markers for colonization studies (Cao et al 2011;Krzyzanowska et al 2012). These studies focus on a basic knowledge between PGPR and the host plant in axenic conditions.…”
Section: Rhizosphere and Root Colonizationmentioning
confidence: 99%